Reconstruction of the Matn Criticism Method Based on Analysis of Variations in Transmission: Formulating a New Approach in Hadith Studies - Nurfaisah N; Tasmin Tangngareng (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Matn criticism in the tradition of Hadith studies is commonly conducted through the assessment of linguistic aspects, rationality, and its relevance to the general principles of Islamic teachings. Such approaches are often interpretative in nature and have not yet formed a systematic analytical framework because they are not based on the entirety of available transmission data. This study aims to propose a methodological reconstruction of matn criticism by employing the analysis of variations in transmission as a new model for examining the validity of Hadith texts. The research is conducted through a literature review of classical and modern references, followed by methodological formulation through stages that include collecting transmission variants, mapping textual differences, examining the context of transmission, and drawing conclusions based on textual consistency. Through this approach, matn examination is carried out comparatively, enabling potential semantic anomalies to be identified more objectively through data comparison rather than solely through theoretical interpretation. The findings indicate that the analysis of transmission variations offers three significant contributions: first, reducing the dominance of subjectivity in matn criticism; second, assisting in the identification of narrations that have undergone textual modification or addition; and third, strengthening semantic evaluation through inter-textual evidence across narrations.